Implementation of Rubber Ball Gripping Exercises on Mr. S with Non-Hemorrhagic Stroke to Increase Muscle Strength at the Darmawan Pavilion, 5th Floor, Gatot Soebroto Army Hospital - Wicaksono, Hendik (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Stroke is one of the diseases that affects the nervous system. Non-Hemorrhagic Stroke is caused by a blockage in the blood vessels which causes a decrease in blood supply to the brain. One of the symptoms that arise due to stroke is a sudden neurological deficit such as muscle weakness which can cause mobility disorders. One of the treatments that can be done is active ROM therapy by holding a ball. This therapy is carried out with a round rubber ball, serrated with elastic properties, can be pressed with force, applied for 15 minutes. Rubber ball holding therapy can stimulate muscle fibers, especially the fingers, to be able to move by practicing gripping and squeezing to stimulate hand movements to help revive brain control over the muscles. During the assessment, the author found that the respondent was experiencing impaired physical mobility. Therefore, the author provides nursing care with non-hemorrhagic stroke, one of which is rubber ball holding exercises. The results obtained were right upper extremity 4444, left upper extremity 5555, right lower extremity 4444 left lower extremity 5555